Food effects on abiraterone pharmacokinetics in healthy subjects and patients with metastatic castration‐resistant prostate cancer. (23rd July 2015) - Chi, Kim N.; Spratlin, Jennifer; Kollmannsberger, Christian; North, Scott; Pankras, Catherine; Gonzalez, Martha; Bernard, Apexa; Stieltjes, Hans; Peng, Lixian; Jiao, James; Acharya, Milin; Kheoh, Thian; et al.
Abstract: Food effect on abiraterone pharmacokinetics and safety on abiraterone acetate coadministration with low‐fat or high‐fat meals was examined in healthy subjects and metastatic castration‐resistant prostate cancer (mCRPC) patients. Healthy subjects (n = 36) were randomized to abiraterone acetate (single dose, 1000 mg) + low‐fat meal,  + high‐fat meal, and fasted state. mCRPC patients received repeated doses (abiraterone acetate 1000 mg + 5 mg prednisone twice daily; days 1–7) in a modified fasting state followed by abiraterone acetate plus prednisone within 0.5 hours post–low‐fat (n = 6) or high‐fat meal (n = 18; days 8–14). In healthy subjects, geometric mean (GM) abiraterone area under plasma concentration–time curve (AUC) increased ∼5‐ and ∼10‐fold, respectively, with low‐fat and high‐fat meals versus fasted state (GM [coefficient of variation], 1942 [48] and 4077 [37] ng · h/mL vs 421 [67] ng · h/mL, respectively). In mCRPC patients, abiraterone AUC was ∼2‐fold higher with a high‐fat meal and similar with a low‐fat meal versus modified fasting state (GM [coefficient of variation]: 1992 [34] vs 973 [58] ng · h/mL and 1264 [65] vs 1185 [90] ng · h/mL, respectively). Adverse events (all grade ≤ 3) were similar, with high‐fat/low‐fat meals or fasted/modified fasting state. Short‐term dosing with food did not alter abiraterone acetate safety.